Nanoparticles in Drug Delivery Systems: Challenges, Innovations, And Surface Modification for Targeted Therapeutics - Abbas, Tasawar; Kanwar, Fatima; Tariq, Hazima; Malik, Muhammad Raza (Indus Journal of Bioscience Research, 2025)
Nanoparticles have become a transforming platform in drug delivery systems. Their remarkable advancement over traditional methods builds upon an improvement in bioavailability, stability, and controlled delivery of therapeutic agents. Here, we discuss the broad spectrum of potential in nanoparticle-based drug delivery systems. Challenges, innovations, and the surface modification strategies that affect their clinical translation are discussed. Notwithstanding the potential they present, challenges including biocompatibility, toxicity, stability, and targeting efficiency persist in restricting their extensive utilization. The review emphasizes recent advancements, including stimuli-responsive nanoparticles, which provide controlled drug release in reaction to environmental triggers, as well as targeted drug delivery, which facilitates the selective accumulation of therapeutic agents at designated sites of disease. Besides, surface modification techniques, such as PEGylation, ligand conjugation, and charge modulation, have been highly promising in improving the stability of nanoparticles, reducing immunogenicity, and enhancing cellular uptake. The future drug delivery systems that are based on nanoparticles will address these challenges through new innovations in nanoparticle design to effect more targeted and effective treatments. While research advances, nanoparticle-based systems are likely to bring revolution in personalized medicine, tailoring medical therapy for different diseases with minimal side effects and better patient outcomes.